-4n+6(5n-1)=72

Simple and best practice solution for -4n+6(5n-1)=72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4n+6(5n-1)=72 equation:


Simplifying
-4n + 6(5n + -1) = 72

Reorder the terms:
-4n + 6(-1 + 5n) = 72
-4n + (-1 * 6 + 5n * 6) = 72
-4n + (-6 + 30n) = 72

Reorder the terms:
-6 + -4n + 30n = 72

Combine like terms: -4n + 30n = 26n
-6 + 26n = 72

Solving
-6 + 26n = 72

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 26n = 72 + 6

Combine like terms: -6 + 6 = 0
0 + 26n = 72 + 6
26n = 72 + 6

Combine like terms: 72 + 6 = 78
26n = 78

Divide each side by '26'.
n = 3

Simplifying
n = 3

See similar equations:

| 5y-6=-29 | | 64.8+18t+4.9t^2=0 | | ((2)2x+9)+((2)1x-5)=50 | | x^2-6-5=0 | | 975=25N | | x-378=0 | | 4(x+4)=5(2x-4) | | 2X^2=3-3X | | ax+7=12-bx | | -5(8+7x)-2x=145 | | 6(1+2m)+m=71 | | (8n+56)-(2n+14)= | | 7r^2+10=80 | | 2x+9(2)+1x-5(2)=50 | | 6(2x+7)=78 | | 1672.992=2*3.14*51.84+2*3.14*7.2*h | | 15319=525+.0575(15319-30000) | | 6(r-5)=-66 | | y=-x(-6) | | 3z^2+17+20=0 | | 3x+2x+5x+5=40 | | 10(x-4)=50 | | 7-7x=7x+5x | | -5(5x-3)+4x=120 | | (5x+6)(7x+7)= | | 2a^2-4=126 | | bx-1=63 | | X-y=c(X) | | 4x+14=9x-35 | | 2y^2+6y+5=0 | | 2(m+3)=4m-k | | 7x-6=-2x+3 |

Equations solver categories